GAMBARAN PEMERIKSAAN DAHAK SEBELUM TERAPI DAN HASIL PENGOBATAN PADA PASIEN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS PRANGGANG KECAMATAN PLOSOKLATEN KABUPATEN KEDIRI - Retno Ardanari Agustin (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2016)
Tuberculosis is a tropical contagious disease, becoming one of the targeted government programs in the eradication of infectious diseases. Tuberculosis may attack a person if exposed to Mycobacterium tuberculosis, which is transmitted through a dropplet infection and lives in an environment with air containing Mycobacterium tuberculosis. The purpose of this study was to determine the results of sputum examination before therapy and tuberculosis treatment results. This study is an Observational Descriptive Epidemiological Study with Cross Sectional Survey approach, using secondary records of Pulmonary TBC 79 patients in Pranggang Community Health Center periode 2013-2015, with descriptive analysis. The result of the research is male patient of 42 people (53,17%), 75 people (94,94%) of OAT drug guidance given Category 1, Classification of tuberculosis of lung of 66 people (83,54%). Sputum examination results before positive therapy of 59 people (74.68%) and the results of treatment of patients cured category 56 people (70.89%). Sputum examination data prior to therapy is Positive, indicating above report number of East Java Provincial Service 2010. Achievement of healing rate of tuberculosis treatment result that is declared cured, under the achievement of East Java in 2010 including achievement targets.